Editorial - Editor, Chief (University of Dar es Salaam Library Journal, 2023)
On behalf of the editorial board, I feel privileged to welcome you to our current issue (vol. 17, no. 2). This issue comprises 12 stimulating articles that reflect the intradisciplinary and interdisciplinary nature of Library and Information Science (LIS).